A luminal EF-hand mutation in STIM1 in mice causes the clinical hallmarks of tubular aggregate myopathy - Celia Cordero-Sanchez; Beatrice Riva; Simone Reano; Nausicaa Clemente; Ivan Zaggia; Federico A. Ruffinatti; Alberto Potenzieri; Tracey Pirali; Salvatore Raffa; Sabina Sangaletti; Mario P. Colombo; Alessandra Bertoni; et al. (The Company of Biologists, 2020)
STIM and ORAI proteins play a fundamental role in calcium signaling, allowing for calcium influx through the plasma membrane upon depletion of intracellular stores, in a process known as store-operated Ca2+ entry. Point mutations that lead to gain-of-function activity of either STIM1 or ORAI1 are responsible for a cluster of ultra-rare syndromes characterized by motor disturbances and platelet dysfunction. The prevalence of these disorders is at present unknown. In this study, we describe the generation and characterization of a knock-in mouse model (KI-STIM1I115F) that bears a clinically relevant mutation located in one of the two calcium-sensing EF-hand motifs of STIM1. The mouse colony is viable and fertile. Myotubes from these mice show an increased store-operated Ca2+ entry, as predicted. This most likely causes the dystrophic muscle phenotype observed, which worsens with age. Such histological features are not accompanied by a significant increase in creatine kinase. However, animals have significantly worse performance in rotarod and treadmill tests, showing increased susceptibility to fatigue, in analogy to the human disease. The mice also show increased bleeding time and thrombocytopenia, as well as an unexpected defect in the myeloid lineage and in natural killer cells. The present model, together with recently described models bearing the R304W mutation (located on the coiled-coil domain in the cytosolic side of STIM1), represents an ideal platform to characterize the disorder and test therapeutic strategies for patients with STIM1 mutations, currently without therapeutic solutions. This article has an associated First Person interview with Celia Cordero-Sanchez, co-first author of the paper.